2022
DOI: 10.3389/fpsyt.2022.997960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate-intensity exercise on social health and physical and mental health of methamphetamine-dependent individuals: A randomized controlled trial

Abstract: ObjectiveMethamphetamine (MA)-dependent individuals’ health problems are widespread and need to be solved urgently. Exercise is considered a potential treatment for MA dependents. The study aimed to determine the effects of a 12-week aerobic exercise on the social, physical, and mental health of MA-dependent individuals.Materials and methodsSixty MA-dependent individuals were randomly assigned into two groups. Subjects in the exercise group (n = 30) received an exercise intervention five days a week for 60 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Furthermore, exercise intervention can help to recover the brain damage (13), facilitate long-term synaptic potentiation-related pathways (14), and promote recovery from severe mental disorders, which was confirmed by realworld multicenter study (15). Exercise has been found to be an effective intervention in improving social health and mental health in people with MUD (16). Moreover, exercise can promote the release of endorphins in the brain, which are naturally occurring analgesics that help to alleviate stress and depression symptoms (17,18).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, exercise intervention can help to recover the brain damage (13), facilitate long-term synaptic potentiation-related pathways (14), and promote recovery from severe mental disorders, which was confirmed by realworld multicenter study (15). Exercise has been found to be an effective intervention in improving social health and mental health in people with MUD (16). Moreover, exercise can promote the release of endorphins in the brain, which are naturally occurring analgesics that help to alleviate stress and depression symptoms (17,18).…”
Section: Introductionmentioning
confidence: 74%
“…In people with mood disorders, aerobic exercise interventions for 8 to 12 weeks have shown some therapeutic efficacy and significant improvement in negative mood (55). A study of 60 methamphetamine-dependent individuals showed that 12 weeks of moderate-intensity aerobic exercise significantly improved the patients' social health, mental health, and physical health (16). Some researchers found that after 8 weeks of moderate-intensity exercise, participants who received exercise interventions had significantly lower depression scores than healthy groups, while participants who received the most frequent exercise had the best results.…”
Section: Negative Emotionsmentioning
confidence: 99%
“…Moderate-intensity exercise can effectively improve mitochondrial function and increase myocardial energy metabolism ( Veeranki et al, 2016 ). Typically, 30–60 min of physical activity positively affects the recovery of many addicted patients ( Xu et al, 2022 ). For example, 30 min of Tai Chi exercise was revealed to increase dopamine concentrations and dopamine receptors, which had a positive effect on reducing drug addiction ( Wang et al, 2022 ); 30 min of moderate-intensity exercise was effective in reducing mobile phone cravings among college students with mobile phone addiction ( Yang et al, 2022 ), providing support for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of treatment, voluntary participation in walking and low-to-moderate-intensity exercise is recommended, as these have protective effects and reduce the risk of injury or other side effects. Moderate-intensity aerobic exercise interventions, including cycling, jogging, callisthenics, and stretching, are effective treatments for methamphetamine-dependent individuals, improving their social, physical, and mental health [ 34 ]. Additionally, moderate-intensity exercise has a higher rate of adherence than intense exercise [ 35 , 36 , 37 ].…”
Section: Integrating Exercise With Therapeutic Approachesmentioning
confidence: 99%